O uso da geometria fractal como ferramenta no ensino de progressões geométricas e logaritmos - Vieira, Diogo Comin (2019)
This essay is a study that seeks to introduce Fractal Geometry as a tool in Geometric Progressions and Logarithms teaching in high school, more precisely in the 1st (first) year, but the presented activities unfold a possibility of application in several Math teaching segments. The goal of this work is to provide theoretical basis and a didactical sequence that reaches several levels of contents mastery, so teachers may work the Fractal Geometry as a motivator agent at teaching and deepening the concepts that were studied in the classroom, also opening the possibility for an approach of themes such as Limits and Convergence of Sequence, even in an intuitive way. This didactical sequence application in the classroom starts with Fractal Cards cutting out, which is a playful (ludic) and funny activity, goes through the relations between Fractal and the subjects studied in high school, up until the development of general formulas and the demand of a certain algebraic mastery, ending in an interesting application of Logarithmic properties.